Caracterización de residuos sólidos urbanos del Cantón Las Naves Provincia Bolívar - Najera Peralta, Katherine Anabeli (2024)
This research involved the characterization of urban solid waste in the Las Naves canton, Bolívar province, using the methodology of Arellano et al. (2012) for urban and socioeconomic characterization, the method of Arellano & Cabezas (2014) to determine the representative sample, and the technique of Arellano et al. (2013) to determine Per Capita Production (PCP), components, and density. In the urban sector of Las Naves canton, 119 residential blocks were identified, divided into four socioeconomic strata: A with 10.08%, B with 64.71%, C with 17.65%, and D with 7.56%. To determine the PCP of solid waste, stratified random sampling was employed, involving 51 households over 7 consecutive days. After applying the box plot test to identify outliers and Tukey's ANOVA to identify significant values, a PCP was obtained for stratum A of 0.69 kg/person/day, stratum B of 0.39 kg/person/day, stratum C of 0.5 kg/person/day, and stratum D of 0.50 kg/person/day, resulting in a weighted PCP of 0.45 kg/person/day. The organic component predominates with 76,83% in the physical composition of USW, followed by potentially recyclable waste at 15,54%, and finally, 0.98% is recyclable waste for the future. The average loose density of solid waste for stratum A is 286.86 kg/m3, stratum B is 277.86 kg/m3, stratum C is 217.00 kg/m3, and stratum D is 220.86 kg/m3, resulting in a weighted loose density of 263.71 kg/m3.